The Influence of Work Discipline, Competency and Physical Work Environment on The Performance of ASN Employees with Job Satisfaction as an Intervening Variable - Umar Ali Lessy Lessy; Made Adnyana (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
-